Identification of thermal properties of hardening concrete by means of evolutionary algorithms - Długosz, Adam; Pokorska, Iwona; Glinicki, Michał A.; Jaskulski, Roman (Computer Assisted Methods in Engineering and Science, 2017)
In this paper, the evolutionary computation procedures for identifying thermophysical properties in hardening massive concrete structures are presented. The heat of cement hydration, thermal conductivity and specific heat are determined for the purpose of modeling temperature evolution in massive concrete elements. Knowledge about temperature fields is very important due to their link with undesirable thermal stresses that can cause a weakening of structures because of thermal cracking. The proposed method is based on point temperature measurements in a cylindrical mould and the numerical solution of the inverse heat transfer problem by means of the finite element method and evolutionary computation.